ORGANIZATIONAL CULTURE AND ORGANIZATIONAL BEHAVIOR OF HIGHER EDUCATION INSTITUTIONS DURING THE COVID-19 PANDEMIC - Pavlova, Sanja (The European Journal of Applied Economics, 2023)
Purpose. The main goal of this paper is to define that, creating culture is essential in any organization and is necessary to know how to act in times of crisis. The creation of culture within an organization requires a structured and meticulous process in its implementation. The process must begin with the definition, by the organization’s leadership team, of those characteristics that will form part of the common behavior of individuals within the company. The desired behaviors are the attitudes, habits, beliefs, values, and forms of interaction that we want to install. In this sense, it is important to think about how we want to be recognized by our customers and employees. Given the situation of COVID-19, we can say that different cultures can determine different behaviors for the same event. Culture is stronger than any business strategy and more influential than any individual member of the company: culture reflects the common behavior of the organization.